Optimal Adaptive Control and Backstepping Control Method with Sliding Mode Differentiator - Shengxin Sun; Yang Zhao; Hao Wu (Complexity)
In order to improve the success rate of space debris object capture, how to increase the resistance to interference in the space robot arm has become an issue of interest. In addition, since the space operation time is always limited, finite-time control has become another urgent requirement needed to be addressed. Considering external disturbances, two control methods are proposed in this paper to solve the control problem of space robot arm. Firstly, a linear sliding mode control method is proposed considering the model uncertainties and external disturbances. The robot arm can track the desired trajectory, while a trade-off between optimality and robustness of the solved system can be achieved. Then, in order to reduce conservativeness and relax restrictions on external disturbances, a novel backstepping control method based on a finite-time integral sliding mode disturbance observer is developed, which compensates for the effects of both model uncertainties and infinite energy-based disturbance inputs. Finally, simulation examples are given to illustrate the effectiveness of the proposed control method.